Study of mechanism of ultrasonic wire bonding process - Zhang, Dong (2008)
In this study, a sensing cum actuating (SCA) technique is developed to study the wire bonding system. The actuating mechanism of a wire bonder is viewed as an SCA device which possesses an unique transduction matrix correlating the electrical input variables of the PZT driver and the mechanical output variables at the tip of the capillary. The transduction matrix is identified experimentally. Thus, the force and velocity at the tip of the capillary is first time obtained from the input voltage and current of the PZT driver.